Analysis of Problem Solving Skills of Class VII Students on Earthquake Material and Mitigation - Rosalia Tunika Grandis; Insih Wilujeng; Suyanta Suyanta (Postgraduate, University of Mataram, 2023)
The variety of levels of student learning motivation causes learning in class not to be implemented optimally even to affect the problem solving process. One of the lessons that emphasize the skills in the form of the ability to solve problems is Natural Sciences (Natural Sciences). Therefore, this research is a tukuk tukuk analyzing the ability to solve the problem of junior high school students in grade VII in Gempta and Mitigation material. This research uses a scientific approach to cooperative learning models. The research design uses pretest and posttest. The pretest results are 54.74% and the posttest average value is 75.73%. Based on the results of the discussion test it can be interpreted that there are significant differences or improvements to the results of the pretest and posttest in both classes of class VII C and VII D. The results of the pretest include the Dalas of the Poor Category. Medium category, while posttest results show good results